2008
DOI: 10.1111/j.1365-3156.2007.01972.x
|View full text |Cite
|
Sign up to set email alerts
|

Low prevalence of HIV and other sexually transmitted infections in young women attending a youth counselling service in Maputo, Mozambique

Abstract: The low prevalence of STI and HIV may be related in part to the high level of awareness registered in the group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 15 publications
3
15
1
Order By: Relevance
“…The SAAJ clinic provides services (free of charge) for young people seeking counseling and treatment for any health problem, but with particular attention to reproductive health and control of sexually transmitted infections (STIs). A low prevalence of STIs and HIV and a high level of awareness has previously been reported in a study performed at the SAAJ clinic [14].…”
Section: Methodsmentioning
confidence: 65%
“…The SAAJ clinic provides services (free of charge) for young people seeking counseling and treatment for any health problem, but with particular attention to reproductive health and control of sexually transmitted infections (STIs). A low prevalence of STIs and HIV and a high level of awareness has previously been reported in a study performed at the SAAJ clinic [14].…”
Section: Methodsmentioning
confidence: 65%
“…A review in 80 developing countries found that youth-friendly services increased young people's use of health services [41]. Interventions in two countries, Mozambique and Madagascar, show that services that include confidential, non-judgemental, convenient and affordable HIV testing and counselling and family planning information and services can increase use of services by youth [42,43]. …”
Section: Reviewmentioning
confidence: 99%
“…A correct diagnosis of a STI is essentials for proper and effective treatment. The concern in the diagnosis and treatment of STIs is not due to the fact that they are infections caused by pathological agents, but also in their possible correlation with increased transition and acquisition of Human Immunodeficiency Virus (HIV) infection [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Information on the prevalence of other sexually transmitted infections in pregnant women in Mozambique is scarce and it is known that these infections during pregnancy can have drastic consequences for pregnancy and for the newborn; they are associated with considerable discomfort and may result in termination of pregnancy, low birth weight and increased infant mortality [33]. Although these infections affect men and women, in developing countries such as Mozambique the situation is very complicated for women for several reasons: women are less able to seek treatment in relation to men, in certain population groups there are social consequences such as stigmatization when women are infertile, including the partner`s right to divorce [11,34]. On the other hand, in these countries complications related to STIs are the major causes of mortality and morbidity of the mother and child during pregnancy [11].…”
Section: Introductionmentioning
confidence: 99%